Merging dualities: How convergence points in art and science can (re)engage women with the STEM field - Forget, Bettina Elisabeth Eva (Canadian Review of Art Education / Revue canadienne d'éducation artistique)

(untitled) (Canadian Society for Education through Art, 2021)
How can the interweaving of knowledge silos help to engage girls who are becoming disinterested in science? This study describes how convergence points in research practices within the fields of art and science can mitigate gender stereotypes associated with the STEM field. A case study of four women working at the intersection of art and science revealed common aspects of their practices: an appreciation of the natural world, a sense of aesthetics, a drawing practice and a reliance on meaningful research questions, suggesting that these can act as bridges between both fields of study.